Asset liquidity and fiscal consolidation programs - Bernardino, Tiago (2019)
We argue that the relationship between wealth inequality and fiscal multipliers depends crucially on the type of fiscal experiment used as well as on the measure of the wealth distribution. We calibrate an incomplete-markets, overlapping generations model to different European economies and use Household Finance and Consumption Survey (HFCS) data to compare fiscal multipliers when models are calibrated to match the distribution of liquid vs. net wealth. We find a negative relationship between fiscal multipliers and wealth inequality when considering fiscal consolidation programs, in contrast to fiscal expansions experiments which are standard in the literature. The underlying mechanism relies on the relationship between the distribution of wealth and the share of credit constrained agents. We examine the role of households’ balance sheet compositions regarding asset liquidity and find that when calibrating the model to match liquid wealth, the relationship between wealth inequality and fiscal multipliers is much stronger.